ORGANIZATIONAL COMMITMENT AND ACHIEVEMENT MOTIVATION ON TEACHER PERFORMANCE IN SCHOOL - Muhammad Ihsan Dacholfany; Adi Susanto (JURNAL AL-TANZIM, 2021)
The purpose of this study was to determine how much influence organizational commitment and achievement motivation have on teacher performance at Muhammadiyah Vocational Schools throughout the city of Metro Lampung. This research is quantitative research with this type of research is causal-comparative research. The population in this study were all teachers of Muhammadiyah Vocational Schools throughout Metro City, totaling 207. The research sample was 67 teachers using the proportional cluster random sampling technique. This research instrument uses a questionnaire. The data analysis technique in this study uses statistical analysis, namely simple and multiple regression analysis and analysis of the coefficient of determination and the F test. The results of this study are organizational commitment and achievement motivation together have a positive and significant effect on teacher performance at SMK Muhammadiyah throughout – Metro City. This is evident from the probability value (p), which is 0.000 < 0.05. The value of the coefficient of determination obtained is 0.590. This means that achievement motivation affects teacher performance by 59.0% and is tested empirically at a significance level of 5%.